2009
DOI: 10.1021/jo9021265
|View full text |Cite
|
Sign up to set email alerts
|

Peloruside B, A Potent Antitumor Macrolide from the New Zealand Marine Sponge Mycale hentscheli: Isolation, Structure, Total Synthesis, and Bioactivity

Abstract: Peloruside B (2), a natural congener of peloruside A (1), was isolated in sub-milligram quantities from the New Zealand marine sponge Mycale hentscheli. Peloruside B promotes microtubule polymerization and arrests cells in the G2M phase of mitosis similar to paclitaxel, and its bioactivity was comparable to that of peloruside A. NMR-directed isolation, structure elucidation, structure confirmation by total synthesis and bioactivity of peloruside B are described in this article. The synthesis features Sharpless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 40 publications
1
62
0
Order By: Relevance
“…The 5-alkylpyrrole-2-carboxaldehydes 16,17,35,36,43,49,60, and 61 were again reisolated from a member of the Mycalidae family, this time from an unidentified M. (Carmia) sp. from Palau together with twelve new mycalenitriles 4-14 (65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75), and seven new mycalazals 14-20 (76-82) [29]. Finally, in 2013, an unidentified Mycale sp.…”
Section: Pyrrole Derivativesmentioning
confidence: 96%
See 3 more Smart Citations
“…The 5-alkylpyrrole-2-carboxaldehydes 16,17,35,36,43,49,60, and 61 were again reisolated from a member of the Mycalidae family, this time from an unidentified M. (Carmia) sp. from Palau together with twelve new mycalenitriles 4-14 (65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75), and seven new mycalazals 14-20 (76-82) [29]. Finally, in 2013, an unidentified Mycale sp.…”
Section: Pyrrole Derivativesmentioning
confidence: 96%
“…Pelorusides share some structural similarity to the geminal dimethyls and polyhydroxylation observed in mycalamides (next section) and the macrolide ring of pateamine (2), however, they are not biochemically related [7]. Peloruside A (3) was active against P388 murine leukaemia cells at approximately 18 nM [7] and peloruside B (107) was active (IC 50 value of 71 nM) against human ovarian carcinoma (1A9 cells) [74]. Pelorusides A-D (3, 107-109) were active against human myeloid leukaemia (HL-60 cells) with IC 50 values of 10 nM, 33 nM, 221 nM, and 2 µM, respectively [71,74].…”
Section: Polyketides Macrolidesmentioning
confidence: 97%
See 2 more Smart Citations
“…Peloruside A is a polyketide isolated from New Zealand marine sponge Mycale hentscheli [23]. Previous studies have shown that Peloruside A causes hyper-stabilization of microtubules by binding to a site on β-tubulin in a manner similar to that of Paclitaxel.…”
Section: Peloruside Amentioning
confidence: 99%